1999
DOI: 10.2134/jeq1999.00472425002800010031x
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification as a Sink for Dissolved Nitrous Oxide in a Freshwater Riparian Fen

Abstract: Denitrification as a sink of dissolved nitrous oxide (N2O) was investigated in a freshwater riparian fen. In a 15‐m transect extending from the hillslope and into the fen the groundwater concentrations of nitrate (NO−3) declined from 1.8 mM NO−3 (25 mg L−1) to less than 0.01 mM NO−3, dissolved oxygen (O2) and nitrous oxide (N2O) declined from approximately 110 µM O2 (3.5 mg O2 L−1) and 4.0 µM N2O‐N (56 µg N L−1), respectively, to zero and the dissolved N2 concentration increased by 589 µM N2‐N (8.2 mg N L−1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 0 publications
3
39
1
Order By: Relevance
“…In addition, riparian zones have been identified as potential sinks for N 2 O (e.g. Blicher-Mathiesen and Hoffmann, 1999;Dhondt et al, 2004). For aquatic systems it was difficult to draw conclusions.…”
Section: N 2 O Emissions From Oceansmentioning
confidence: 99%
“…In addition, riparian zones have been identified as potential sinks for N 2 O (e.g. Blicher-Mathiesen and Hoffmann, 1999;Dhondt et al, 2004). For aquatic systems it was difficult to draw conclusions.…”
Section: N 2 O Emissions From Oceansmentioning
confidence: 99%
“…Various workers (Tiedje 1988;Patrick and Jugsujinda 1992;Achtnich et al 1995;Blicher-Mathiesen and Hoffmann 1999) have reported that NO 3 À reduction occurs mainly when subsurface water DO falls below 0.5-1.6 mg O 2 /L.…”
Section: Wetland Sediment Physical and Chemical Characteristics And Pmentioning
confidence: 99%
“…Owing to the special hydrological, hydrochemical and ecological conditions in these ecosystems, wetlands are generally considered to possess a high potential for nutrient retention, nutrient transformation, flood protection and biodiversity (e.g. Devito et al, 1989;Johnston et al, 1990;Leonardson et al, 1994;Blicher-Mathiesen and Hoffmann, 1999;Rosenblatt et al, 2001). However, wetland restoration measures often fail due to the rather incidental selection of sites and water management measures, mainly caused by neglecting the geohydrological characteristics (landscape position) of the specific wetland (Bedford, 1999;Zedler, 2000).…”
Section: Introductionmentioning
confidence: 99%